Crisis? What (Type) of Crisis? The overlapping problems of the European Union - Lehmann, Kai (Revista de Sociologia e Política, 2014)
It is common today, even in the European media, to treat the current crisis of the European Union almost exclusively as an economic crisis. The present article pretends to show that such a focus is not only wrong but is indeed dangerous for the future development of the European Union as a whole. The article will argue that the present economic crisis simply aggravated – and a lot – a crisis of legitimacy through which the European Union has been passing for some time. Showing that the anti-European tendencies which are spreading throughout the countries of the continent threaten the very future of the European project, the article will make suggestion on reforms for the future development of the EU, alerting to the necessity to finally elaborate once again a coherent argument for the continuation of the European integration process which puts the European population at the heart of the political process instead of just austerity.